Socio-Economic and Governance Impacts of Cross-Border Policies on Indo-Nepal Border Communities - Srivastava, Sanjay; Chaurasiya, Sneha; Ghimire, Shiva Raj (Journal of Development Review, 2025)
This research examines the socio-economic dynamics, migration patterns, and governance challenges along this unique border, utilizing data from 134 respondents collected through structured questionnaires. This study highlights the mutual benefits of an open border policy, including enhanced trade, seasonal migration, and cultural integration, which sustain livelihoods and strengthen bilateral relations. However, it also identifies significant challenges, such as poverty, infrastructural deficiencies, wage disparities, and environmental vulnerabilities, including deforestation and flooding. Trade relations remain pivotal, with India being Nepal’s largest trading partner. Informal trade and remittances from Nepalese workers in India contribute significantly to Nepal's economy. Conversely, Indian industries benefit from labor supplied by Nepalese migrants. Despite this interdependence, security policies and geopolitical tensions often disrupt cross-border interactions, creating economic and social challenges for communities. The study finds that regulatory inconsistencies and infrastructural inadequacies impede seamless integration, whereas geopolitical disputes strain historically robust ties. This paper calls for harmonized policies that address the socioeconomic and environmental needs of border populations while balancing security concerns. Improved governance, equitable labor rights, and investments in infrastructure are critical to fostering sustainable development and mitigating vulnerabilities. This study underscores the importance of bilateral cooperation in addressing these challenges and enhancing the shared prosperity of Indo-Nepal border communities by applying a mixed-method approach, where surveys were conducted and thematic analysis was done with the focus group